2004
DOI: 10.1084/jem.20040341
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Turnover of Effector–Memory CD4+ T Cells in Healthy Humans

Abstract: Memory T cells can be divided into central–memory (TCM) and effector–memory (TEM) cells, which differ in their functional properties. Although both subpopulations can persist long term, it is not known whether they are maintained by similar mechanisms. We used in vivo labeling with deuterated glucose to measure the turnover of CD4+ T cells in healthy humans. The CD45R0+CCR7− TEM subpopulation was shown to have a rapid proliferation rate of 4.7% per day compared with 1.5% per day for CD45R0+CCR7+ TCM cells; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
169
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(189 citation statements)
references
References 28 publications
18
169
0
2
Order By: Relevance
“…Simulations predict sharp decline of effective clonal diversity. We simulated the population dynamics of human naive T cells as described in the text and Materials and Methods, based on experimental estimates of the Hayflick limit (22,29), the bias in thymic production of different T-cell clones (46,47), and the rates of thymopoeisis (9,18,19,21), T cell turnover (42,43,45), and telomere attrition (31,48). We set the bias in thymic production of different T cell clones to w = 0.01.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Simulations predict sharp decline of effective clonal diversity. We simulated the population dynamics of human naive T cells as described in the text and Materials and Methods, based on experimental estimates of the Hayflick limit (22,29), the bias in thymic production of different T-cell clones (46,47), and the rates of thymopoeisis (9,18,19,21), T cell turnover (42,43,45), and telomere attrition (31,48). We set the bias in thymic production of different T cell clones to w = 0.01.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted, using a population-dynamic modeling approach based on experimental data (18,21,22,28,29,31,38,42,43,(46)(47)(48), that the markedly lower effective clonal diversity found in elderly humans results from the fact that each T cell can divide for only a limited number of times before it reaches replicative senescence (or the Hayflick limit) (29,63) and is consequently eliminated (28,36,37). This, coupled to the facts that thymic production of new T cells declines substantially with age (11,18,19) and that T cells will undergo compensatory proliferation (38,40,64) to fill the empty homeostatic space created by the loss of senescent cells, leads to a sharp fall in effective clonal diversity at approximately the same time as was empirically observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo labeling with stable isotopes in combination with appropriate mathematical analysis of these data provides a way to obtain T cell decay and production rates and to follow the fate of recently produced T cells. Data on stable isotope labeling of naïve and memory human T cells (18)(19)(20)(21)(22) are available, but several short-comings of these studies hamper their interpretation: (i) the short-term labeling period, which did not allow for sufficiently high labeling levels of naïve cells (19,21,22); and (ii) the lack of delabeling curves in long-term labeling studies (20), which would have shown whether recently produced T cells contribute to the T cell pool under investigation or rapidly disappear by death or activation; and (iii) the frequent use of the precursor-product relationship (20,23,24), leading to underestimation of the extent of T cell turnover (25). Using the precursor-product relationship one measures the net accrual of label and ignores the possibility that cells were produced and lost during the labeling period because of a short life span.…”
mentioning
confidence: 99%